Dual-ligand mediated one-pot self-assembly of Cu/ZnO core/shell structures for enhanced microwave absorption. Issue 48 (26th April 2016) - Cheng, Yi-Feng; Bi, Han; Wang, Chao; Cao, Qi; Jiao, Wenling; Che, Renchao
Abstract : A facile one-pot method has developed to assemble Cu/ZnO core/shell nanocrystals with different aspect ratios for enhanced microwave absorption. Besides, the one-pot method has shown the appreciable yields and no cumbersome multistep operations. Abstract : Encapsulation of a Cu core into a ZnO shell has been rarely reported by a one-pot method, which is expected to be a novel combination of a reflection core and a dielectric microwave absorber. Here, a facile one-pot strategy has been developed for assembling Cu/ZnO core/shell nanocomposites with different sizes and aspect ratios. The temperature acts as the switch for starting ZnO encapsulation in this strategy, and the sizes and aspect ratios of the resultant nanocomposites depend sensitively on the heating rate in 220–250 °C. The different morphologies and structures of the nanocomposites have been characterized comprehensively, and the relevant growth mechanism is also discussed in this paper. The microwave absorption performances in both as-synthesized Cu@ZnO products (spherical-like and rod-like shapes) are significantly enhanced by comparing with that of pure ZnO due to the enhanced interfacial scattering and dielectric interface polarization in the ZnO shell. This one-pot method can complement for rational methodology in constructing metal/semiconductor core/shell nanocomposites.